Delegitimasi Tradisi melalui Bingkai Penafsiran al-Qur’an: Analisis Model Dakwah Konservatif Channel YouTube RodjaTV - Dwi Putra, Imam Muhajir; Hamdani, Moh. Salman; Wijaya, Roma; MS, Moh Hisyam (Sunan Kalijaga Islamic State University, 2023)
The textual interpretation of various Quranic verses, particularly those relating to Indonesian societal traditions, reflects an ideological approach that is disseminated through the RodjaTV YouTube channel. The oral explanation of these meanings shapes the listener's perception, leading them to accept the presented interpretation as an accurate reflection of reality. This study aims to uncover the mechanisms through which tradition is integrated into the interpretation of Qur'anic verses. Employing a qualitative method with framing analysis, the research reveals that the explanation of verse meanings—particularly when directly connected to the context of the verse or the historical narrative of the people addressed—creates an analogy with Indonesian traditions. This analogy produces a discursive alignment that suggests a similar treatment and punishment are warranted. This core framing is presented in a unified narrative that serves to validate the perspective offered. The emerging imagery is reinforced through common phrases like “returning to the Qur'an” and “returning to the Sunnah”. The depiction of tradition as analogous to the realities faced by the communities mentioned in the verses is further emphasized by the repeated use of terms such as kafir (unbeliever), misguided, and ghalw (excessiveness). In this framework, desacralization occurs not through the distortion of specific terms, but by forming analogies that equate the targeted subjects of the verses with the traditions practiced in Indonesian society. As a result, these traditions are portrayed as parallel to the disbelief and transgressions of the earlier communities, who were the original focus of the Quranic verses.